Studying from the Sofa. Contribution to the HoGe conference 2018 "Digital learning and teaching" / Studieren vom Sofa aus.Beitrag zur HoGe-Tagung 2018 "Digitales Lernen und Lehren" - Beck Eva Maria; Bluemke Christine; Holweg Wibke; Borde Theda (Sciendo, 2019)
A new bachelor course of study started at 01.10.2018. It's an online offer for competence development in interprofessional cooperation. The target group are professionally experienced health professionals from therapy and care. By the end of July 2020, the extra-occupational study format, the media didactic online-based concept and the contents will be tested and evaluated. The continuing development of technology-supported learning/teaching scenarios will be incorporated into the further development of the online study ofering, as will the evaluation results from the pilot phase of the course.